Implementasi PMK No.40 Tahun 2017 tentang Jenjang Karier Profesional Perawat Rumah Sakit Islam Surabaya - Muhadi Muhadi (Center for Health Policy and Management, 2021)
The development of a nurse's career path needs attention for hospital management because it will affect the quality of service. RSI nurses have not been optimal in participating in training related to professional competence. The purpose of this study was to analyze the Implementation of Professional Career Paths for Nurses in RSI Surabaya. This research is qualitative, where this qualitative research is to see and try to understand social problems based on facts obtained in the field (exploration). Determination of the number of informants in 5 structural officials using purposive sampling technique. This study the authors use triagulation of data collection, data validity (trustworthiness) in qualitative research can be done using inspection techniques, which are based on criteria, namely: degree of trust (credibility), uncertainty (confirmability), dependability (dependability) and transferability (transferability). The conclusion of this study is that the implementation of PMK No.40 of 2017 concerning the professional career path of nurses is not optimal. The process of increasing the level of nurse competence is carried out and in accordance with the guidelines by the nursing committee but the guidelines need to be updated. Job promotion is carried out with the peer group assessment approach, personal relationships and emotional closeness with nursing staff who are the suggestions and targets. RSI's attention to the needs and professional career development of nurses is very limited and has not been optimized. Nursing committees create old guidelines that have not been adapted to new policies. PMK No.40 2017 concerning the professional career paths of nurses at RSI is focused on clinical nurses and nurse managers in stages. Keywords: Professional Career Path, Policy Implementation Patterns, Competence, Nurse